PROFESIONALISME APARATUR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN WONOGIRI - Nuryanto, Nuryanto (Jurnal Ilmu Administrasi Publik, 2018)
This research was intended to describe the degree of apparatusprofessionalism among the employees at the Capital Investment and OneStop Service Agency in Wonogiri Regency. This research is descriptiveresearch type. Purposive sampling technique was employed to select theinformants. Primary data was derived from the selected informants;meanwhile the secondary data was collected from several resorces suchas books, written reports, minutes meetings, and other related documents.Interview and observation were used as the data collecting techniques.This research used creativity, inovation, and responsiveness as thedimensions of professionalism variable. Related to the dimension ofcreativity, research result indicated that the employees have alreadyconveyed new and positive ideas, however, those ideas did notimplemented due to budget limitation, human resources limitation, anddue to existing regulation. Employees worked rigidly and highly depend oninstruction coming from above level. Dealing with inovation dimension,research result indicated that the employees had already used newestinformation technology for supporting their tasks and their works. Therewas sustainable placement of the employees on the basis ofcompetencies. Related to the degree of responsiveness, it was found thatthe employees already developed good attitude to serve community atbest. It was however, policies and work programs became obstacles tocover optimally community aspirations and needs. Based on researchfinding, it can be concluded that the degree of professinalism measuredby the degree of creativity and of responsiveness was still low. However,the degree of innovation dimension, it was found had alreary be well done.Based on the research result, it is recommended that the promotion ofapparatus resources by promoting their educational level and trainings isstill needed. It is also recommended that work program reflected instrategic planning and in work planning should be oriented on communityneeds and to meet better public servises.Key words: professionalism; creativity; innovation; responsiveness.